Imigrantes africanos no Brasil contemporâneo: fluxos e refluxos da diáspora - Rodrigues, Ester Fatima Vargem (2014)
The present work on African immigration to Brazil in contemporary presents some aspects of my involvement with insertion in this subject, and brings up the question of the various forms and strategies that some African populations are able to cross the Atlantic, reviving diasporas. Was based on analysis of information from newspaper that made references to African immigrants , found in various forms to enter the ships anchored on the African coast, and thus achieve maximize their life chances . It also establishes dialogues with African immigrants who arrived here, in many different ways and times, with varying personal characteristics about their impressions about meanings that traverse the twenty-first century. Concludes with an overview of the political situation in Africa as well as the relationships that Brazil has established with African countries